Efficacy of Sutures of the Ala Bases and in the Form of V-Y Labial in Patients Subject to the Surgically Assisted Expansion of Maxila (International Journal of Medical and Surgical Sciences, 2017)
This study aimed to evaluate the effects of the Nasal Alar Bases suture (N.A.B.S.) and V-Y lip suture (V-Y.L.S.) in the maintenance of the distance between the nasal alar bases (N.A.B.) and the red lips display (R.L.D.) in patients operated for correction of crossbite with maxillary atresia. We evaluated 9 patients, 4 who received the above mentioned sutures, and 5 who received simple sutures. It was evaluated the measures N.A.B. and R.L.D. in the preoperative phase, postoperative, and after 7 and 450 days. Measurements of N.A.B. were stable throughout the experimental period in N.A.B.S. and V-Y.L.S. group, while the group receiving simple sutures there was an increase of this measure in the postoperative period and a decrease after 450 days. The N.A.B.S. and V-Y.L.S. group showed a significant increase in R.L.D. in immediate postoperative period, reducing slightly after 7 days, and presenting a significant loss in the final assessment, showing an even lower value than the mean preoperative. N.A.B.S. was effective in the short and medium term in controlling unwanted nasal enlargement in patients undergoing E.M.C.A. In the immediate postoperative period, there is an increased R.L.D., but long-term reduction of the R.L.D. occurs in all E.M.C.A. patients, regardless of the type of suture used.